Avaliação da contribuição de desenvolvedores para projetos de software usando mineração de repositórios de software e mineração de processos - Costa, Daniel Alencar da (2013)
Software Repository Mining (MSR) is a research area that analyses software repositories in order to derive relevant information for the research and practice of software engineering. The main goal of repository mining is to extract static information from repositories (e.g. code repository or change requisition system) into valuable information providing a way to support the decision making of software projects. On the other hand, another research area called Process Mining (PM) aims to find the characteristics of the underlying process of business organizations, supporting the process improvement and documentation. Recent works have been doing several analyses through MSR and PM techniques: (i) to investigate the evolution of software projects; (ii) to understand the real underlying process of a project; and (iii) create defect prediction models. However, few research works have been focusing on analyzing the contributions of software developers by means of MSR and PM techniques. In this context, this dissertation proposes the development of two empirical studies of assessment of the contribution of software developers to an open-source and a commercial project using those techniques. The contributions of developers are assessed through three different perspectives: (i) buggy commits; (ii) the size of commits; and (iii) the most important bugs. For the opensource project 12.827 commits and 8.410 bugs have been analyzed while 4.663 commits and 1.898 bugs have been analyzed for the commercial project. Our results indicate that, for the open source project, the developers classified as core developers have contributed with more buggy commits (although they have contributed with the majority of commits), more code to the project (commit size) and more important bugs solved while the results could not indicate differences with statistical significance between developer groups for the commercial project